Positive blood alcohol is associated with reduced DVT in trauma. Issue 1 (January 2015) - Cook, Mackenzie R.; Louis, Scott G.; McCully, Sean P.; Stucke, Ryland S.; Fabricant, Sonya P.; Schreiber, Martin A.
Abstract: Introduction: Trauma patients exhibit a complex coagulopathy which is not fully understood and deep venous thrombosis (DVT) rates remain high. The effects of alcohol (EtOH) consumption on coagulopathy in trauma patients have not been studied. We hypothesized that acute EtOH intoxication would produce a relative hypocoagulable state as measured by thrombelastography (TEG) and would be associated with reduced DVT rates. Methods: Data were prospectively collected on 213 trauma patients at a level 1 trauma centre and analyzed in a retrospective secondary analysis. Thrombelastography (TEG), standard laboratory tests and ETOH levels were performed. If the level was positive, patients were grouped as EtOH+ and all patients were screened for DVT using a standard protocol. Statistical significance was p < 0.05. Results: The EtOH+ group was predominantly male (76%), was younger ( p < 0.05), had a lower BMI ( p < 0.05), demonstrated a lower AIS extremity score ( p < 0.01) and was less likely to have a blunt injury ( p < 0.01) than the EtOH− group. Gender, ISS and other AIS scores were not significantly different. TEG values in the alcohol group demonstrated a relative hypocoagulable state that was associated with a reduced DVT incidence, 1.4% versus 16.2%, ( p < 0.01). This difference was not detected with conventional assays. A multivariate logistic regression was performed, controlling for common risk factors for DVT and a positive EtOH level on admission was independently associated with reduced DVT incidence. Conclusions: Alcohol consumption is associated with a relative hypocoagulable state on TEG that is associated with a decreased DVT incidence. This difference is not detected by conventional assays.